2020
DOI: 10.1016/j.clnu.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Reduced skeletal muscle protein balance in paediatric Crohn's disease

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication Title: Reduced skeletal muscle protein balance and sarcopenia in paediatric Crohn's disease patients in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 71 publications
(84 reference statements)
0
25
1
1
Order By: Relevance
“…Research has shown that elevation of serum cytokines, such as tumor necrosis factor- α (TNF- α ) and interleukin 6, reduces insulin-like growth factor-1 (IGF-1) in the serum and muscle of CD patients. This reduction, in turn, results in growth hormone resistance in the liver and skeletal muscle, leading to a downward moderation of the mTOR pathway into activation of the ubiquitin ligand and expression of proteolytic enzyme, which cause skeletal muscle mass reduction and impairment of muscle contraction [ 13 , 14 ]. Current interventions for sarcopenia include exercise therapy, nutrition therapy, and medication.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that elevation of serum cytokines, such as tumor necrosis factor- α (TNF- α ) and interleukin 6, reduces insulin-like growth factor-1 (IGF-1) in the serum and muscle of CD patients. This reduction, in turn, results in growth hormone resistance in the liver and skeletal muscle, leading to a downward moderation of the mTOR pathway into activation of the ubiquitin ligand and expression of proteolytic enzyme, which cause skeletal muscle mass reduction and impairment of muscle contraction [ 13 , 14 ]. Current interventions for sarcopenia include exercise therapy, nutrition therapy, and medication.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Lean mass was determined by the balance between muscle protein synthesis and breakdown, but loss of lean mass driven by inflammation and a suboptimal muscle protein synthetic response to enteral nutrition, termed anabolic resistance, may destroy this mechanism and finally lead to reduced lean mass. 29 Recently, Davies and colleagues 30 confirmed the theory in adolescent CD patients that inability to respond to nutrition could be implicated in low muscle mass in CD. Those CD patients with anabolic resistance cannot maintain a positive protein balance, even in remission.…”
Section: Discussionmentioning
confidence: 94%
“…The precise mechanism of muscle deficits in CD remains unclear, with some suggesting impaired muscle protein synthesis [43,44], potentially linked to reduced systemic IGF-1 [44].…”
Section: Discussionmentioning
confidence: 99%